An effective UFLC-MS/MS method used to study pharmacokinetics of major constituents of Fukeqianjin formula in rat plasma - Kanghua Wang; Lu Liu; Yanfang Yang; Xiaoyan Liu; Lei Zhang; Wei Xu; Yingtao Zhang; Xiuwei Yang; Peng Zhang; Kaifeng Peng; Yun Gong; Nifu Liu (BMC, 2020)
Abstract Background Fukeqianjin formula (FKQJF) is a Chinese medicine prescription, which has been widely used individually or in combination with other western medicine for the treatment of various gynecological inflammatory diseases, including chronic cervicitis, chronic pelvic inflammatory disease and endometritis, so on and so force. Methods The ultra-fast liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UFLC-MS/MS), a quick and efficient method was established and applied to quantify the major constituents of Fukeqianjin formula in rat plasma, and its pharmacokinetics of oral absorption was studied. Nineteen components in Fukeqianjin formula were detected and identified as the major compounds absorbed into the blood according to their chromatographic behavior, molecular weight, ion fragments and other information of these compounds. Furthermore, the plasma drug concentration-time curves were established and the related kinetic parameters were analyzed. Results The results showed that all the 19 compounds could be rapidly absorbed by the gastrointestinal tract, the plasma drug concentration of most compounds could reach a peak at around 1-2 h, and the double-peaks on behalf of the enterohepatic circulation were found in most drug concentration-time curves. The method used in this experiment was validated comprehensively including specificity, linearity, precision, accuracy, stability, matrix effect, and recovery. Conclusions These results showed that the developed method was suitable for pharmacokinetic analysis of the main components of Fukeqianjin formula in rat plasma, and may provide useful information for the subsequent distribution studies in vivo.